Dampak Pengimplementasian Kurikulum 2013 terhadap Performa Siswa Sekolah Menengah Pertama - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of this study is to determine the contribution of principal transformational leadership, teaching performance of teachers, and the learning culture towards achievement of madrasah aliyah. Correlational survey is used as the method of the research with 274 sample of teachers .The sampling techniques used are area sampling, proportional sampling and random sampling. Questionnaire used as the instrument to be analyzed by using descriptive and inferential statistics. The results of this study indicate: 1) the level of achievement of the madrasah, principal transformational leadership, teaching performance of teachers and learning culture is good; 2) transformational principal leadership contributes positively and significantly towards achievement of madrasah aliyah; 3) teacher performance in teaching contributes positively and significantly towards achievement of madrasah aliyah; 4) learning culture contributes positively and significantly towards achievement of madrasah aliyah: 5) transformational principal leadership, teacher performance in teaching and learning culture contribute positively and significantly towards achievement of madrasah aliyah. Accordingly, increasing the principal transformational leadership, teaching performance of teachers and the culture of learning leads to the improvement of madrasah achievement.ABSTRAK Penelitian ini bertujuan untuk mengungkapkan informasi empirik tentang seberapa kuat dampak implementasi Kurikulum 2013 terhadap performa siswa SMP. Daerah penelitian mencakup 44 kabupaten/kota dengan sampel sebanyak 82 sekolah yang melibatkan responden sebanyak 1804 siswa. Teknik penelitian yang digunakan adalah penelitian deskriptif. Analisis data dilakukan dengan menggunakan analisis deskriptif. Hasil penelitian menunjukkan, bahwa implementasi Kurikulum 2013 di SMP berdampak positif terhadap performa siswa ditandai dengan dampak sikap spiritual dan sikap sosial yang dimiliki siswa seperti senang melaksanakan ibadah agama, pendidikan akal budi, berinteraksi dalam keragaman, kebersamaan, kerukunan, senang berkata benar, berani mengakui kesalahan, dan senang menjaga kebersihan juga senang membantu teman yang menghadapi kesulitan nampak makin berkembang. Selain itu, transformasi pengetahuan dan keterampilan siswa untuk menjadi bangsa yang cerdas, produktif, kreatif, dan inovatif untuk mengantisipasi dan memperoleh solusi yang tepat dalam rangka pemecahan masalah, beradab, dan terhormat mengindikasikan semakin berkembang.